Classic Testicular Seminoma in Men Aged 50 Years or Over: A Case Report and Review of the Literature - Rawad Abou Zahr; Khalil Chalhoub; Imad Matta; Sawsan Horani; Zarouhie Bedoyan; Georges El Hachem; Imad Ghantous; Michel Jabbour (Case Reports in Urology)
Testicular cancer is the most frequent solid tumor detected in young adult men. Germ cell tumors (GCTs), particularly seminomas, are the most common type of testicular neoplasms seen in that age population. Most publications have reported decreasing incidence of GCTs in patients above forty years of age. Since the biologic activity of seminomas appears similar across ages, recommended management of senior adults involves a multimodal therapy of radical inguinal orchiectomy with radiation or cytotoxic treatment as needed. Attenuating chemotherapy dosages are critical to ensure better tolerability of associated adverse events. Here we report a case series of 2 men older than fifty years of age with metastatic testicular seminoma. We aim to emphasize a rare clinical entity encountered in the senior adult population.